The ADONIX study - Torén, Kjell; Olin, Anna-Carin (University of Gothenburg, 2012)
"ADONIX" is an acronyme for "Adult-onset asthma and nitric oxide" and is the collective name for the population study conducted by the Department of Occupational and Environmental Medicine, University of Gothenburg. 6685 randomly selected persons aged 25-75 years, have participated. The ADONIX study collaborates with the INTERGENE study and the PURE study, both at the University of Gothenburg.
The study examines the prevalence of airway inflammation using exhaled nitric oxide (NO) by putting this in relation to the concentration of small particulates in the air on the particular day the measurement was made and the days before. Air pollution data are imported from Gothenburg Environmental Administration and other municipalities in Västra Götaland. Measurement of nitric oxide in exhaled air may eventually become a good test to diagnose asthma or other lung disease. The subjects also do a lung function test (spirometry), and answer questions concerning background factors such as recent job, allergies, asthma and heredity, and the current exposure of different kinds of air pollution both indoors and outdoors.
In addition, anthropometric measurements, measurement of body composition, ECG, blood tests and questionnaires on lifestyle factors (in collaboration with INTERGENE and PURE).
Follow up with a new survey is planned to start 2013.

Purpose:

The original primary aim was investigating whether increased fraction of exhaled nitric oxide (FENO) is associated with an increased risk for new-onset asthma. This has been extended to an overall aim to increase the understanding of the interactions between different risk factors and genetic susceptibility in the mechanisms and prognosis for asthma and chronic obstructive pulmonary disease (COPD), coronary heart diseases and stroke.

2490 of the participants are also part of the INTERGENE study

"ADONIX" står för "Adult-onset asthma and nitric oxide" och är samlingsnamnet för den populationsstudie som Enheten för Arbets- och miljömedicin vid Göteborgs Universitet bedriver. 6685 slumpmässigt utvalda personer i åldern 25-75 år i Västra Götaland har deltagit. ADONIX-studien samarbetar med INTERGENE-studien och PURE-studien, båda också vid Göteborgs Universitet.
I studien undersöks förekomsten av luftvägsinflammation med hjälp av utandad kväveoxid (NO) genom att sätta detta i relation till halten av små partiklar i omgivningsluft just den dagen mätningen görs och dagarna innan. Luftföroreningsdata hämtas från Göteborgs Miljöförvaltning och andra kommuner i Västra Götaland. Mätning av kväveoxid i utandningsluft kan på sikt bli ett bra test att diagnosticera astma eller annan lungsjukdom. Försökspersonerna gör även ett lungfunktionstest (spirometri) och besvarar frågor rörande bakgrundsfaktorer såsom tidigare arbetsuppgifter, allergiska besvär, astma och ärftlighet, samt om aktuell exponering av olika sorters luftföroreningar såväl inom- som utomhus.
Dessutom ingår antropometriska mått, mätning av kroppssammansättning, EKG, blodprov samt enkäter med frågor om bl a livsstilsfaktorer (i samarbete med INTERGENE och PURE).
Uppföljning med ny undersökning är planerad att påbörjas 2013.

Syfte:

Det ursprungliga primära syftet var att undersöka om ökad kväveoxidhalt i utandningsluft (FENO) är associerat med en ökad risk för nydebuterad astma. Detta har utvidgats till ett övergripande mål att öka förståelsen för samspelet mellan olika riskfaktorer och genetisk sårbarhet i mekanismer och prognos för astma och kronisk obstruktiv lungsjukdom (KOL), hjärt-kärlsjukdomar och stroke.

2490 av deltagarna ingår även i INTERGENE-studien
ADONIX-studien
Keywords: Diagnosis; Diagnos; Anthropometry; Antropometri; Blood Specimen Collection; Blodprovstagning; Body Composition; Kroppssammansättning; Respiratory Tract Diseases; Luftvägssjukdomar; Dyspnea; Andnöd; Life Style; Livsstil; Electrocardiography; Elektrokardiografi; Socioeconomic Factors; Socioekonomiska faktorer; Asthma; Astma; Noise; Buller; Cough; Hosta; Nitric Oxide; Kväveoxid; Air Pollution; Luftförorening; Respiratory Tract Infections; Luftvägsinfektioner; Drug Utilization; Läkemedelsförsörjning; Rhinitis, Allergic, Seasonal; Årstidsbunden allergisk rinit; Smoking; Rökning; Disease; Sjukdom; Sick Leave; Sjukfrånvaro; Particulate Matter; Luftburna partiklar; Spirometry; Spirometri; Pets; Sällskapsdjur; Occupational Exposure; Yrkesmässig exponering; Heredity; Ärftlighet; Hypersensitivity; Överkänslighet; HEALTH; HÄLSA; Respiratory Medicine and Allergy; Lungmedicin och allergi